Prevalence of IgG antibodies against Malawi polyomavirus in patients with autoimmune diseases and lymphoproliferative disorders subjected to bone marrow transplantation - Nicol, Jérôme T. J.; Mazzoni, Elisa; Iaquinta, Maria Rosa; De Pace, Raffaella; Gaboriaud, Pauline; Maximova, Natalia; Cason, Carolina; De Martino, Eleonora; Mazziotta, Chiara; Coursaget, Pierre; Touzé, Antoine; Boz, Valentina; et al. (Frontiers in Immunology, 2024)
Introduction: Human polyomaviruses (HPyVs) cause persistent/latent infections in a large fraction of the population. HPyVs infections may cause severe diseases in immunocompromised patients. Malawi Polyomavirus (MWPyV) is the tenth discovered human polyomavirus (HPyV 10). MWPyV was found in stool samples of healthy children. So far, the few investigations carried out on HPyV 10 did not find an association with human disease.Methods: In this study, to verify the putative association between MWPyV and human diseases, the MWPyV seroprevalence was investigated in patients affected by (i) lymphoproliferative disorders (LPD), (ii) immune system disorders, i.e. autoimmune diseases (AD) and in (iii) healthy subjects . An indirect ELISA., employing virus-like particles (VLP) to detect serum IgG antibodies against MWPyV/HPyV 10, was carried out. The study also revealed the prevalence of another polyomavirus,Results: Sera from patients with distinct autoimmune diseases (n= 44; mean age 20 y) had a prevalence of MWPyV antibodies of 68%, while in patients with lymphoproliferative disorders (n=15; mean age 14 y), subjected to bone marrow transplantation, the prevalence was 47%. In healthy subjects (n=66; mean age 13y) MWPyV antibodies prevalence was 67%. Our immunological investigation indicates that (i) MWPyV/HPyV 10 seroconversion occurs early in life and MWPyV/HPyV 10 appears to be another polyomavirus ubiquitous in the human population. A significant lower MWPyV antibody reactivity together with a lower immunological profile, were detected in sera of LPD patients compared to HS2 (*p<0.05), (Fisher's exact test). LPD and AD patients have a similar MCPyV seroprevalence compared to healthy subjects.Discussion: MWPyV seroprevalence indicates that this HPyV is not associated with lymphoproliferative and autoimmune diseases. However, the ability to produce high levels of antibodies against MWPyV appears to be impaired in patients with lymphoproliferative disorders.Immunological investigations indicate that MWPyV seroconversion occurs early in life. MCPyV appears to be an ubiquitous polyomavirus, as other HPyVs, in the human population.